“They made space for me”: Enhancing receptive generosity in an Anglican Diocese in Aotearoa New Zealand - Rivera, Catherine (Ecclesial Futures, 2023)
Drawing on 16 months of ethnographic fieldwork with young, Anglican social justice activists in Aotearoa New Zealand, this article engages with Romand Coles’s theory of receptive generosity, and the theme of the western church as marginal, to explore why a particular Anglican Diocese was attracting new, millennial aged members, most of whom did not grow up Anglican. I consider how spaces of generous reciprocity were formed and enabled through living in intentional communities (ICs) and being able to engage with pluralistic ‘broad table’ spaces of discussion and dissent. These factors were part of what drew the research participants to this Diocese and to Anglicanism in general, as well as enhancing their social justice activism. My research shows the importance of intentionally making spaces of belonging for millennials and Gen Z aged people in a faith community, rather that hoping the status quo of the past will suffice.